Functional gluten-free beverage elaborated from whole quinoa and defatted chia extruded flours: antioxidant and antihypertensive potentials - Sánchez Magaña, Luis Martín; Reyes Moreno, Cuauhtémoc; Garzón Tiznado, José Antonio; Milán Carrillo, Jorge; Gómez Favela, Mario Armando; Cuevas Rodríguez, Edith Oliva; Espinoza Moreno, Ramona Julieta; Gutiérrez Dorado, Roberto (Acta Universitaria, 2022)
The current market demands gluten-free (GF) foods with better nutritional/nutraceutical value. In this study, a functional GF beverage (GFB) from a flours mixture of optimized extruded quinoa (OEQ) (70%) and extruded defatted chia (EDC) (30%) was developed. To obtain OEQ, a central composed experimental design with two factors (extrusion temperature [TE] = 60 °C-140 °C and screw speed [VT] = 60 rpm-240 rpm) and three responses (antioxidant activity [AoxA], total phenolic compounds [TPC], and in vitro protein digestibility [IVPD]) was used. The optimal extrusion conditions for OEQ were 138 °C/138 rpm, and for EDC they were 147 °C/237 rpm (obtained in a previous work). The mixture had calculated protein efficiency ratio (C-PER) = 2.28 and angiotensin-converting enzyme (ACE) inhibitory potential (IC50) = 0.271 mg/ml. 200 ml of functional GFB contains 5.61 g of good quality protein, 6.13 g of dietary fiber, 88 kcal, and AoxA = 5091 µmol TE. The functional GFB is a healthy alternative for celiac people.